Editorial [Hot topic:Pigment Epithelium-Derived Factor (PEDF) in Health and Disease (Guest Editor: Sho-Ichi Yamagishi)] - Yamagishi, Sho-Ichi (Current Molecular Medicine, 2010)
Pigment epithelium-derived factor (PEDF) is a glycoprotein that belongs to the superfamily of serine protease inhibitors. It was first purified from the conditioned media of human retinal pigment epithelial cells as a factor with potent neuronal differentiating activity. Recently, PEDF has been shown to be a highly effective inhibitor of angiogenesis in cell culture and animal models. Further, we, along with others, have found that PEDF is a multifunctional secreted protein; it possesses complex neuroprotective, anti-oxidative, anti-inflammatory, antithrombogenic, insulin-sensitizing properties, any of which could potentially be exploited as a therapeutic option for the treatment of a variety of disorders, including neurodegenerative disorder, angiogenic eye disease, neoplasms, hyperpermeable renal-retinal disorder, cardiometabolic disease, diabetes and its vascular complications and various bone diseases. However, as far as we know, there are few comprehensive reviews to summarize the pathophysiological role of PEDF in health and disease. I believe that this issue is helpful for most of the researchers in the field of biochemistry, molecular biology, tumor cell biology, vascular cell biology, endocrinology and cardiology who would like to understand the role of PEDF and its clinical implications in various devastating disorders. In this issue, I would like to reinforce the emerging knowledge regarding PEDF as a novel biomarker and therapeutic target in vivo.